(untitled) (Eurasian Journal of Engineering and Technology, 2023)
In the field of mobile networks, characterized by their dynamic and often unpredictable nature, this article explores cutting-edge advances in adaptive video conferencing. Our innovative solution addresses these challenges by integrating a mobile application with a bandwidth monitoring module, a video compression module specifically designed for mobile network conditions, and an AES encryption module to ensure the security of the data exchanged. On the server side, we took a virtualized approach, leveraging virtual machines (VMs) and Docker, to improve scalability and resource efficiency. This comprehensive approach aims to address the challenges posed by changing network conditions, providing users with an adaptive and seamless video conferencing experience, regardless of bandwidth variations and network unforeseen events. By exploring the integration of mobile-specific modules and server virtualization, this research contributes to the ongoing dialogue on optimizing video communication in the dynamic mobile network landscape. In terms of performance, our solution aims to provide optimal video quality by dynamically adjusting the resolution based on the available bandwidth. Video compression by interpolation optimizes bandwidth usage without compromising visual quality too much. Additionally, server virtualization ensures efficient resource management, thereby improving the scalability of the application to meet growing demands. This comprehensive approach results in a more reliable, adaptable and secures video conferencing experience, redefining the standards of communication in the complex context of mobile networks